Figure 2 from: Li Y-M, Shivas RG, Li B-J, Cai L (2019) Diversity of Moesziomyces (Ustilaginales, Ustilaginomycotina) on Echinochloa and Leersia (Poaceae). MycoKeys 52: 1-16. https://doi.org/10.3897/mycokeys.52.30461 - Li, Ying-Ming; Shivas, Roger G.; Li, Bao-Ju; Cai, Lei (Zenodo, 2019)
Figure 2 a–dMoesziomyceskimberleyensis (holotype BRIP 51843) e–gMoesziomycesglobuligerus (BRIP 27384) h–kMoesziomycesantarcticus (HMAS 60130). a, b: sori. c, d, f, j, k: spores under LM. g: spores under SEM. Scale bars: 1 mm (b, i); 10 µm (c, d, f, g, j, k).